Building Resilient Workforces: The Role of Safety and Social Needs in Employee Retention - Shinde, Shilpa (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Employee retention remains a critical challenge for organizations across industries, with high turnover adversely affecting productivity, costs, and organizational knowledge. This paper explores the significant role of psychological needs—specifically safety and social needs—in influencing employee retention. Drawing on foundational motivation theories, it examines how factors such as job security, financial stability, safe working conditions, belongingness, team cohesion, recognition, and inclusive culture impact employees’ intent to stay, engagement, and loyalty. The study emphasizes that addressing these needs holistically enhances organizational commitment and reduces attrition. Practical recommendations for HR managers and leaders are provided, including strategies to strengthen safety and social needs through workplace safety programs, clear communication, mentorship, team-building, and inclusive policies. The paper concludes that prioritizing psychological needs is essential for building resilient, motivated workforces and sustaining long-term organizational success.